ANALISIS MODEL 4As PADA KESEDIAAN MENGGUNAKAN KREDIT USAHA RAKYAT - Rofikoh Rokhim; Iin Mayasari (Universitas Gadjah Mada, 2018)
The development of the business world is not only dominated by big business actors, but also medium, small, and even micro. These micro-scale business actors are given the opportunity to thrive. People Business Credit Program (Kredit Usaha Rakyat) is applied as an innovative product that is specifically for micro entrepreneurs. This research aims to study four approaches of availability, affordability, awareness, and acceptability to analyze the willingness of using microfinance credit. This research uses a quantitative approach and multiple regression for the data analysis. The long-term goal of this research is to provide input for higher decision makers, companies, and local governments to develop better welfare and partnership strategies. This research found that the willingness of using microfinance credit was influenced by availability, awareness, and willingness to accept, except of affordability variable.